Sustainable tourism in the Isle of Man - Canavan, Brendan (2010)
The Isle of Man was once a busy, upmarket tourism destination, but it has declined dramatically since its 1950's heyday. This project reviews the possibilities for tourism development in a small island on the periphery of the UK and Europe. Research of island stakeholders gauges demand for tourism revival and what is sought from this. Sustainable tourism is recommended as most suitable for meeting island needs, reducing impacts and exploiting the locations cultural and natural resources to create an appealing product for niche visitors. Practical recommendations for implementing such a strategy are provided.